Os processos estruturantes no âmbito da Jurisdição Constitucional: a construção da decisão adequada por meio do diálogo institucional - AROUCHE JUNIOR, Deomar da Assenção (2021)
This dissertation aims to study the process of the structural litigation on the Constitutional Jurisdiction. It has been analyzed the origins of this category of American law based on the doctrine and concrete cases decided by the Supreme Court of the United States of America. Another cases of the comparative law from countries as Argentina, Colombia, South Africa and India were analyzed. After that, some points as constitutional interpretation, judicial activism, judicial review and topics related to the democratic legitimacy of the Judiciary action were approached. Whereas that in the last decades various structural injunction about inefficiency of the State has been filled on the Supremo Tribunal Federal, it makes necessary a profound analysis of the processing of those actions. For this reason, the present study analyzed the evolution of the techniques of implementation of decisions made in structural injunctions in the comparative law in order to verify the applicability in the Brazilian law. In this sense, it was sought to investigate the mechanisms available in the Brazilian procedural law that can be applied to give more efficiency to structural litigation. In those investigations it was found a tendency to sought a solution to structural litigations through dialogical mechanisms without, however, giving up more intense intervention measures. According the cases decided by the Brazilian Supremo Tribunal Federal, it is almost a consensus about the fact that the measures to effectuate a decision, must be chosen for each case considering their particularities but always looking forward the participation of others players in the construction of the solution.